ANIMAL WELFARE LAWS IN INDIA - Srinibas Nayak, Maithili Chaudhury (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This research paper discusses the Animal welfare laws and the mind-set of people with regard to the animals, of how these co species are perceived by the humans in order for them to be able to treat animals as they do. The paper also discusses the deeper attributes related to the abuse of animal and how such abuse is a manifestation of mental illnesses. It has been found that more often than not, animal abuse also leads to unleashing of violence among fellow human beings. The paper discusses the need to value animals and the laws that exist in the country that ensure animal safety. It talks about the lack of awareness that prevails in the society regarding the rights of the animals. Some of the provisions of the Prevention of Cruelty to animals Act, 1960 have also been discussed. The paper concludes with discussing one of the landmark judgements which called for some of the animal rights being declared as the fundamental rights.